2020
DOI: 10.1093/noajnl/vdaa082
|View full text |Cite|
|
Sign up to set email alerts
|

Characterizing benefit from temozolomide in MGMT promoter unmethylated and methylated glioblastoma: a systematic review and meta-analysis

Abstract: Background The current standard of care for the management of patients with newly diagnosed glioblastoma (GBM) includes maximal safe resection followed by radiotherapy (RT) with concurrent and adjuvant temozolomide (TMZ). While it is well established that TMZ has better efficacy in patients with MGMT promoter methylation, it remains an area of debate whether TMZ should be omitted when treating GBM patients with unmethylated MGMT. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…A recent meta-analysis confirms initial data and found a median overall survival (OS) of about 14 months as compares to 24 for patients with unmethylated and methylated GBM, respectively. Progression-free survival (PFS) was almost doubled in methylated (10 months) compared to unmethylated patients (about 5 months) (2). However, the irrefutable value of MGMT promoter methylation as a prognostic and predictive marker has not therapeutic reverse: lack of methylation does not translate into changes in therapeutic algorithms to date.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis confirms initial data and found a median overall survival (OS) of about 14 months as compares to 24 for patients with unmethylated and methylated GBM, respectively. Progression-free survival (PFS) was almost doubled in methylated (10 months) compared to unmethylated patients (about 5 months) (2). However, the irrefutable value of MGMT promoter methylation as a prognostic and predictive marker has not therapeutic reverse: lack of methylation does not translate into changes in therapeutic algorithms to date.…”
Section: Introductionmentioning
confidence: 99%
“…Although glioblastomas generally have high expression of this gene which makes them largely resistant to the effect of TMZ, some of these cell lines have reduced gene expression. This is usually due to promoter methylation, and these have notably higher sensitivity to TMZ [200]. However, CAP application enhanced this cytotoxic effect, even in cell lines with highly expressed MGMT [201], and this cytotoxic effect was comparable with that in cell lines with methylated MGMT.…”
Section: Temozolomidementioning
confidence: 98%
“…Promoter methylation of the O-6-Methylguanine-DNA Methyltransferase (MGMT) gene is a prognostic marker in patients with glioma because MGMT methylation leads to better response to alkylating agents, such as TMZ (198). Indeed, patients harboring MGMT-methylated GBMs had a 10-month and 4month higher median overall and PFS, respectively, compared with MGMT-non-methylated patients (199). Interestingly, two different groups showed that MGMT-methylated gliomas presented a lower autophagy risk score compared with MGMTnon-methylated patients (136,137).…”
Section: Autophagy Activation As a Response To Internal Stimulimentioning
confidence: 99%